Is bank misconduct related to social capital? Evidence from U.S. banks - Martin-Flores, Jose M. (Journal of Banking & Finance, 2024)
This paper investigates whether social capital plays a role in bank misconduct. I find that U.S. banks headquartered in high social capital areas, as indicated by the strength of civic norms and the density of social networks, are less likely to face enforcement actions. This relationship is mainly significant for banks with a lower geographical dispersion, and it holds in a range of robustness and endogeneity tests. I run additional tests based on classes of enforcement actions, components of social capital, risk-taking, opacity, and bank actions associated with negative externalities. These tests deliver results supporting the idea that the main findings of the paper are largely attributed to social capital's role in exerting external discipline, which prevents misconduct-related behaviors in banks.